The Impact of Corporate Social Responsibility on Employees of Manufacturing Firms in Nigeria (Global Journal of Management and Business Research, 2023)
In recent years multiple authors have explored the connection between Corporate Social Responsibility CSR activities and employee performance specifically in regards to employee engagement commitment and satisfaction This study examine the impact of CSR on the employees performance in the Nigeria manufacturing sector Social exchange theory which posited that reciprocity plays a crucial role in shaping relationships within organizations was used to underpin the study Descriptive statistics inform of frequency count and percentage will be applied to analyze the research questions formulated in this study while inferential statistics in form of regression analysis was employed to test the hypotheses postulated in this study Findings showed a significant effect of corporate and social responsibility on the engagement of the employees in the Nigeria manufacturing sector Result also indicated a significant impact of CSR on employees commitment in the Nigeria manufacturing sector
Keywords: corporate social responsibility; engagement; commitment; satisfaction; employee; manufacturing sector